Evaluating treatment effect on interferon-alpha in female patients with systemic lupus erythematosus: a case-control study - Ruaa Hameed Abdulridha; Asmaa Mohammed Saud; Mohammed Hadi Alosami (Journal of the Pakistan Medical Association, 2024)
a